The Lord's Prayer in Matthew and in John - Walker, Wm O. (New Testament studies, 1982)
Similarities have occasionally been noted between the so-called ‘High Priestly Prayer’ of Jesus in the Fourth Gospel and the ‘Lord’ Prayer’ as found in Luke and, more particularly, in Matthew and the Didache.